Sezonska dinamika debelinske rasti dreves - Gričar, Jožica (Gozdarski vestnik, 2009)
Numerous studies are currently being carried out on the seasonal dynamics of wood formation, but similar studies on secondary phloem are rare. The influence of certain climatic factors on the mechanism of xylem and phloem ring growth formation can be studied on trees that are growing in their natural environment or under experimentally controlled conditions. Intra-annual information on radial growth of trees are very important for modeling in dendroclimatological and dendroecological studies for better use and interpretation of climate proxies that are stored in ring widths and features. This paper gives a description of radial growth of trees and cambialactivity, and a brief overview of the studies of intra-annual wood formation currently being carried out in Europe, and the potential of phloem formation research.
Keywords: ksilogeneza; floem; les; kambij; celična diferenciacija